Improving Students' Reading Comprehension Through PQ4R Strategy - Ayu Arisna Arifuddin (CV. Publikasi Indonesia, 2025)
Reading comprehension is a key skill for academic success and facing global challenges. As the importance of English literacy increases, students need effective strategies to understand different types of texts. This study aims to improve students' reading comprehension through PQ4R (Preview, Question, Read, Reflect, Recite, and Review) strategy in class 12 Ap 1 SMK YPLP PGRI 1 Makassar. The PQ4R strategy is an elaboration technique that helps students understand and remember information from reading texts. The method used was Classroom Action Research (PTK) conducted in two cycles, including planning, action, observation, and reflection stages. Data were collected through reading comprehension tests, observations, and interviews. The results showed that the PQ4R strategy significantly improved students' reading comprehension in descriptive and narrative texts. The average students' reading comprehension score increased from 49% in the initial test to 57% in the first cycle, and reached 78% in the second cycle for descriptive text. Meanwhile, students' comprehension of narrative text increased from 51% in the initial test to 68% in the first cycle, and reached 79% in the second cycle. In addition, the PQ4R strategy also increased students' participation and motivation in learning English reading skills. Thus, the PQ4R strategy can be used as an alternative in teaching English reading at vocational level to help students understand texts more effectively and improve their reading skills.